2021
DOI: 10.3390/jof7020090
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Genetic Determinants of Methanol Tolerance in Yeast Suggests Differences in Methanol and Ethanol Toxicity Mechanisms and Candidates for Improved Methanol Tolerance Engineering

Abstract: Methanol is a promising feedstock for metabolically competent yeast strains-based biorefineries. However, methanol toxicity can limit the productivity of these bioprocesses. Therefore, the identification of genes whose expression is required for maximum methanol tolerance is important for mechanistic insights and rational genomic manipulation to obtain more robust methylotrophic yeast strains. The present chemogenomic analysis was performed with this objective based on the screening of the Euroscarf Saccharomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 98 publications
0
18
0
Order By: Relevance
“…Genes related to chitin and glucan synthesis, namely CHS1 (chitin), FKS1 (β1,3-glucans), ACF2 (β1,3-glucans), and KRE6 (β1,6-glucans), as well as genes involved in cell wall integrity ( PUN1 ) and cell wall organization ( SIT4 ), were also found to be involved in ethanol tolerance ( Kubota et al, 2004 ; Auesukaree et al, 2009 ; Teixeira et al, 2009 ; Mota et al, 2021 ). The upregulation of FKS1 and also of SED1 and SMI1 genes, involved in cell wall biosynthesis depends on the Znf1 transcription factor, recently implicated in adaptation to ethanol stress ( Samakkarn et al, 2021 ).…”
Section: Yeast Response and Tolerance To Industrially Relevant Stress...mentioning
confidence: 99%
See 3 more Smart Citations
“…Genes related to chitin and glucan synthesis, namely CHS1 (chitin), FKS1 (β1,3-glucans), ACF2 (β1,3-glucans), and KRE6 (β1,6-glucans), as well as genes involved in cell wall integrity ( PUN1 ) and cell wall organization ( SIT4 ), were also found to be involved in ethanol tolerance ( Kubota et al, 2004 ; Auesukaree et al, 2009 ; Teixeira et al, 2009 ; Mota et al, 2021 ). The upregulation of FKS1 and also of SED1 and SMI1 genes, involved in cell wall biosynthesis depends on the Znf1 transcription factor, recently implicated in adaptation to ethanol stress ( Samakkarn et al, 2021 ).…”
Section: Yeast Response and Tolerance To Industrially Relevant Stress...mentioning
confidence: 99%
“…A recent chemogenomic analysis reported that, in S. cerevisiae , methanol and ethanol, share genetic determinants of tolerance involved in cell wall maintenance ( Mota et al, 2021 ). Methanol is a feedstock alternative to sugar-based raw substrates for biorefinery processes and a toxic compound commonly found in crude glycerol, a by-product of the biodiesel industry, and in hydrolysates from pectin-rich biomass residues ( Yasokawa et al, 2010 ; Martins et al, 2020 ; Mota et al, 2021 ). Methanol and ethanol tolerance genes include FKS1 and SMI1 (β1,3-glucan synthesis), ROT2 (β1,6-glucan synthesis), MNN11 (mannosylation of CWPs), and WSC1 (CWI pathway membrane sensor).…”
Section: Yeast Response and Tolerance To Industrially Relevant Stress...mentioning
confidence: 99%
See 2 more Smart Citations
“…The ubiquitin-proteasome system controls almost all basic cellular processes-such as progression through the cell cycle, signal transduction, cell death, immune responses, metabolism, protein quality control and development-by degrading short-lived regulatory or structurally aberrant proteins, connecting ubiquitylation and autophagy as key regulatory events in proteasome quality control [49,50] . In Saccharomyces cerevisiae, several genes involved in DNA repair (eight RAD genes) that have been identi ed as speci c for methanol toxicity were previously reported as determinants of tolerance for formaldehyde, a methanol detoxi cation pathway intermediate [51] . Knockdown of FLD and FGH allows the accumulation of formaldehyde, leading to upregulation of DNA repair genes.…”
Section: Effect Of Dna Cross-linking On Proteasome and Peroxisomementioning
confidence: 99%